From Sediment to Top Predators: Broad Exposure of Polyhalogenated Carbazoles in San Francisco Bay (U.S.A.) - Wu, Yan; Tan, Hongli; Sutton, Rebecca; Chen, Da (Environmental science & technology, 2017)
The present study provides the first comprehensive investigation of polyhalogenated carbazoles (PHCZs) contamination in an aquatic ecosystem. PHCZs have been found in soil and aquatic sediment from several different regions, but knowledge of their bioaccumulation and trophodynamics is extremely scarce. This work investigated a suite of 11 PHCZ congeners in San Francisco Bay (United States) sediment and organisms, including bivalves (n = 6 composites), sport fish (n = 12 composites), harbor seal blubber (n = 18), and bird eggs (n = 8 composites). The most detectable congeners included 3,6-dichlorocarbazole (36-CCZ), 3,6-dibromocarbazole (36-BCZ), 1,3,6-tribromocarbazole (136-BCZ), 1,3,6,8-tetrabromocarbazole (1368-BCZ), and 1,8-dibromo-3,6-dichlorocarbazole (18-B-36-CCZ). The median concentrations of ΣPHCZs were 9.3 ng/g dry weight in sediment and ranged from 33.7 to 164 ng/g lipid weight in various species. Biomagnification was observed from fish to harbor seal and was mainly driven by chlorinated carbazoles, particularly 36-CCZ. Congener compositions of PHCZs differed among species, suggesting that individual congeners may be subject to different bioaccumulation or metabolism in species occupying various trophic levels in the studied aquatic system. Toxic equivalent (TEQ) values of PHCZs were determined on the basis of their relative effect potencies (REP) compared to 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD). The median TEQ was 1.2 pg TEQ/g dry weight in sediment and 4.8–19.5 pg TEQ/g lipid weight in biological tissues. Our study demonstrated the broad exposure of PHCZs in San Francisco Bay and their characteristics of bioaccumulation and biomagnification along with dioxin-like effects. These findings raise the need for additional research to better elucidate their sources, environmental behavior, and fate in global environments.